SIFAT FISIKOKIMIA PADA YOGHURT BUAH NAGA MERAH (Hylocereus polyrhizus L.) DENGAN PENAMBAHAN BERBAGAI LEVEL SUSU SKIM - Devi Arifani; Siti Rahmawati Zulaikhah; S. A. Chayatul Luthfi (Jurnal Ilmu dan Teknologi Peternakan, 2023)
Yoghurt is a pasteurized milk product that is fermented using lactic acid bacteria (LAB). Theaddition of dragon fruit juice aims as a natural colorant in yoghurt, in addition dragon fruitcontains antioxidants such as vitamin C, flavonoids and polyphenols. The use of skim milk inyoghurt can increase the viscosity, aroma, acidity and protein. The purpose of the study was to determine the effect of giving skim milk with different levels in red dragon fruit yoghurt on physicochemical properties yogurt (pH value, acidity level and viscosity).. This study was carried out using a completely randomized design (CRD) using 4 treatments and 5 replications, if there is a difference between treatments, a further test is carried out, namely DMRT analysis. The treatment in this study was the addition of various levels of skim milk (0%, 3%, 6% and 9% w/v). The parameters observed were pH, acidity and viscosity of red dragon fruit yoghurt. The result showed that the addition of various levels of skim milk had no significant effect (P>0.05) on pH and acidity levels, but there was a significant effect on viscosity (p<0.05). The conclusion of this study was that the addition of skim milk at levels of 0%, 3%, 6%, and 9% (w/v) had no effect on pH and acidity, but had an effect on the increasing viscosity of red dragon fruit yogurt. Key Word: Skim Milk, Acidity Level, pH Test, Viscosity, Red Dragon Fruit Yogurt